JavaScript and JSON essentials: successfully build advanced JSON-fueled web applications with this practical, hands-on guide - Sriparasa, Sai Srinivas (Community experience distilled., 2013)
The book follows a tutorial-based approach and will teach you how to work with JSON tools, design JSON objects, and how to use different techniques to handle JSON data.This book is a great resource for developers who would like to learn more about JSON and who wish to apply it in their own projects. It will be useful to have some prior knowledge of HTML and JavaScript to help you understand the concepts covered in this book. Some familiarity with a server-side language such as PHP, C#, or Python would also be beneficial, but this is not compulsory.